1999
DOI: 10.1088/0022-3727/32/13/307
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the N2O dissociation in a RF discharge reactor

Abstract: In situ diagnostic measurements and reactor modelling are used to study the N2O dissociation by radio frequency (RF) discharges. Measurements are undertaken at 0.5 and 1 Torr gas pressure with a RF power density varying from 4.2 to 35.7 mW cm-2. The reactor modelling involves an electrical discharge model coupled to hydrodynamic and mass transfer models. Only an electrical discharge model accounting for the negative ion conversion from O- to NO- and the subsequent electron detachment allow a good coherence bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 42 publications
8
48
2
Order By: Relevance
“…The calculated data for α/p coincide with previous measured [17] and calculated [18] data. The values of the attachment coefficient, η/p, we obtained are in satisfactory agreement with previous experimental [17] and calculated [18] data. Figure 7 shows the calculated dependence of the average electron energy, ε e on the reduced field, E/p, which is in satisfactory agreement with previous experimental [13] and calculated [20] values.…”
Section: Figuresupporting
confidence: 88%
See 2 more Smart Citations
“…The calculated data for α/p coincide with previous measured [17] and calculated [18] data. The values of the attachment coefficient, η/p, we obtained are in satisfactory agreement with previous experimental [17] and calculated [18] data. Figure 7 shows the calculated dependence of the average electron energy, ε e on the reduced field, E/p, which is in satisfactory agreement with previous experimental [13] and calculated [20] values.…”
Section: Figuresupporting
confidence: 88%
“…The solid curve presents the data calculated with the Bolsig code, solid circles are for our measured data (from the turning points), empty circles are for our measured data (from the minima), solid triangles are for the experimental data from [17], empty triangles are for the experimental data from [16], solid squares are for the experimental data from [15], empty squares are for the experimental data from [14] and solid diamonds are for the experimental data from [19]. The dashed curve presents the calculation data from [18].…”
Section: Electron Drift Velocity Determination From Rf Breakdown Curvmentioning
confidence: 99%
See 1 more Smart Citation
“…1 (a)). The dissociation analysis of the N 2 O molecules in a discharge plasma performed by Date et al [18] reveals that NO and N can be minor dissociated products besides the more abundant N 2 and O 2 . Also, Pai et al [19] have shown that N impurities and Si-H and N-H bonding groups that could be removed by adding He to the PECVD gas mixture.…”
Section: Optimizationmentioning
confidence: 99%
“…Consequently, it is of considerable interest to study the properties of rf capacitive discharges in pure N 2 O. However, published results are scarce, 13,14 and present only 3 V W characteristics together with discussions of the molecular dissociation. The process of N 2 O dissociation was also studied experimentally and theoretically.…”
Section: Introductionmentioning
confidence: 99%